2022
DOI: 10.3390/admsci12030082
|View full text |Cite
|
Sign up to set email alerts
|

Different Preferences or Opposite Directions? Reforms and Job Satisfaction at Public and Private Universities in Spain

Abstract: Recent decades have witnessed how both in Spain and elsewhere, legal reforms have helped to transform the management and governance of Higher Education Institutions (HEIs). These transformations have changed the conditions in which academics work, with a knock-on effect on their job satisfaction. Although these legal developments in Spain have basically been the same for both the public and private sectors in Higher Education, the evidence gathered in this article shows that the rate of cases of loss of job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
0
0
Order By: Relevance
“…This may be because private universities generally have more access to private funding and resources for investing in technology and developing their faculty members, thus allowing their professors to dedicate more time to developing their digital skills and participating in continuing education programs. In fact, a study conducted in Spanish public and private universities on professors' satisfaction regarding the latest administrative and political changes in universities revealed that professors from public universities were more unsatisfied than their peers from private universities; this is likely due to the bureaucratization of the public sector, reinforcing the care that university management must have with such issues that can hinder or delay processes (Olaskoaga-Larrauri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because private universities generally have more access to private funding and resources for investing in technology and developing their faculty members, thus allowing their professors to dedicate more time to developing their digital skills and participating in continuing education programs. In fact, a study conducted in Spanish public and private universities on professors' satisfaction regarding the latest administrative and political changes in universities revealed that professors from public universities were more unsatisfied than their peers from private universities; this is likely due to the bureaucratization of the public sector, reinforcing the care that university management must have with such issues that can hinder or delay processes (Olaskoaga-Larrauri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%